Sociodemographic characteristics and reproductive health factors associated with maternal knowledge and practice of infection prevention in neonates in North Dayi District, Ghana - Tuglo, Lawrence Sena; Agyekum, Benjamin Adu; Darku, Edward Delali; Alida, Natabou Morine; Seelo, Kitso Palesa; Magaga, Khauhelo; Chiambiro, Kudzai Victor; Tuglo, Jessica Dzigbordi; Sakre, Sylvia Mawusinu; Otoo, Desmond Dzidzornu; Gmanyami, Jonathan Mawutor (Frontiers in Public Health, 2023)
Abstract Background: Neonates are at major risk of infection, but data on the knowledge and practice of infection prevention in neonates (IPNs) are scarce. This study aimed to assess sociodemographic characteristics and reproductive health factors associated with the knowledge and practice of IPNs among mothers. Methods: This was a multicenter cross-sectional study conducted among 612 mothers. A structured questionnaire was used for data collection adapted from previous studies. Univariate analyses were performed to determine the association between the knowledge and practice of IPNs and the mother’s sociodemographic characteristics and reproductive health factors. Results: Analysis showed that less than half of the mothers (12.9%) had poor knowledge of IPNs, while 21.6% incorrectly practiced it. Poor knowledge of IPNs was associated with ages less than 25 years, having secondary education, primiparous mothers, home delivery and mothers who had babies with complications after birth. Likewise, the poor practice of IPNs was linked to ages less than 25 years, income level between GHc200 and GHc500, primiparous mothers, fewer than four antenatal clinic (ANC) visits, fewer than three postnatal clinic (PNC) visits and mothers who had good knowledge of IPNs. Conclusions: Less than half of the mothers had poor knowledge and poor practice of IPNs according to the WHO’s guidelines. The District Health Directorate of North Dayi should encourage the use of IPN guidelines by the WHO for outreach and campaigns.